2019
DOI: 10.1200/jco.18.02459
|View full text |Cite
|
Sign up to set email alerts
|

Binimetinib, Encorafenib, and Cetuximab Triplet Therapy for Patients With BRAF V600E–Mutant Metastatic Colorectal Cancer: Safety Lead-In Results From the Phase III BEACON Colorectal Cancer Study

Abstract: PURPOSE To determine the safety and preliminary efficacy of selective combination targeted therapy for BRAF V600E–mutant metastatic colorectal cancer (mCRC) in the safety lead-in phase of the open-label, randomized, three-arm, phase III BEACON Colorectal Cancer trial ( ClinicalTrials.gov identifier: NCT02928224; European Union Clinical Trials Register identifier: EudraCT2015-005805-35). PATIENTS AND METHODS Before initiation of the randomized portion of the BEACON Colorectal Cancer trial, 30 patients with BRAF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
135
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(140 citation statements)
references
References 47 publications
2
135
0
3
Order By: Relevance
“…Targeting a dominant RTK-driven adaptive feedback reactivation is an attractive strategy to suppress adaptive resistance, as it intercepts the critical feedback loop at its most upstream point. Indeed, in BRAF V600 colorectal cancer, targeting EGFR-the RTK thought to be the primary driver of feedback reactivation from preclinical studiesin combination with BRAF inhibition, has led to an improvement in clinical efficacy (34)(35)(36)(37)(38)(39). However, preclinical and clinical data have demonstrated that other RTKs can drive feedback in an EGFRindependent manner, and that the combination of BRAF and EGFR only suppresses signaling in a subset of patients (34).…”
Section: Discussionmentioning
confidence: 99%
“…Targeting a dominant RTK-driven adaptive feedback reactivation is an attractive strategy to suppress adaptive resistance, as it intercepts the critical feedback loop at its most upstream point. Indeed, in BRAF V600 colorectal cancer, targeting EGFR-the RTK thought to be the primary driver of feedback reactivation from preclinical studiesin combination with BRAF inhibition, has led to an improvement in clinical efficacy (34)(35)(36)(37)(38)(39). However, preclinical and clinical data have demonstrated that other RTKs can drive feedback in an EGFRindependent manner, and that the combination of BRAF and EGFR only suppresses signaling in a subset of patients (34).…”
Section: Discussionmentioning
confidence: 99%
“…In the BEACON study (45), patients with CRC and the BRAF V600E mutation, who had experienced treatment failure with one or two prior chemotherapy regimens, were recruited and treated with three molecular target agents, encorafenib (a BRAF inhibitor), binimetinib (a MEK inhibitor) and cetuximab (an EGFR inhibitor). In 29 patients with BRAF V600E mutant tumors, the overall response rate was 48%, the median progression-free survival was 8.0 months and the median OS time was 15.3 months (45). This indicates that the BRAF V600E mutation serves as a facilitator of CRC progression and therapies are required that inhibit the feedback activation of RAS-RAF signal cascade.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the most effective treatment strategy for patients with stage IV CRC and BRAF mutations, which may be associated with high miR-31 expression levels (13), is currently unknown. The answer may exist in a recent clinical trial for unresectable patients with BRAF V600E mutant CRC, called the BEACON study (45). BRAF inhibition has been revealed to improve clinical outcomes in patients with melanoma and non-small cell lung cancer that have a BRAF V600 mutation; however, in patients with CRC, BRAF inhibition has only conferred a marginal improvement in the reduction of tumor burden (46)(47)(48)(49)(50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the combination of vemurafenib, irinotecan and panitumumab/ cetuximab has now been included in the National Comprehensive Cancer Network (NCCN) guidelines for the second line therapy of BRAF mutant CRC patients [29,30]. Similarly, other combinatorial strategies including BRAFi and EGFRi paired with MEK inhibitors have shown improvement in patients' survival in randomized clinical trials and have been included in consensus guidelines [29][30][31][32]. Our study aimed to explore the effectiveness of different targeted drugs either alone or in combination in BRAF V600E cell lines, with the aim to shed light on the possible mechanisms driving resistance to biological therapy in BRAF mutant patients.…”
Section: Discussionmentioning
confidence: 99%